What is special about indexical attitudes?. Issue 7 (3rd October 2018) - Valente, Matheus
Abstract: In this paper, I assess whether indexical attitudes, e.g. beliefs and desires, have any special properties or present any special challenge to theories of propositional attitudes. I being by investigating the claim that allegedly problematic indexical cases are just instances of the familiar phenomenon of referential opacity. Regardless of endorsing that claim, I provide an argument to the effect that indexical attitudes do have a special property. My argument relies on the fact that one cannot account for what is it to share someone else's indexical attitudes without rejecting some plausible thesis about propositional attitudes. In the end, I assess Herman Cappelen and Josh Dever's considerations on intentional action and extract an argument from them that could – if successful – neutralize my own. I finish by arguing that their argument has an important flaw, thus failing to convince us that indexical attitudes are just as ordinary as any other.